Usability of "MyClassRoom" Application for E-Learning during the Pandemic - R. I. E. Saragih (International Journal of Information System and Innovative Technology, 2022)
The pandemic, which is happening all over the world, forces higher education institutions to conduct their learning process online. Lecturers are required to be ready to use technology nowadays and able to use e-learning as interesting effectively as possible, in order to increase the motivation and learning outcomes of students. There are several e-learning systems available on the internet that could be used for teaching. Unfortunately, those systems are not suitable for some reasons. The main reason is that each higher education institution has its own unique learning process. There is an e-learning system called “MyClassRoom” which is designed based on the context of the user. The results were made using a Likert scale. From the measurement results it can be concluded that the application which is used as e-learning in the study program has usability value and is very good.